2018
DOI: 10.1093/jxb/ery327
|View full text |Cite
|
Sign up to set email alerts
|

Can zinc pollution promote adaptive evolution in plants? Insights from a one-generation selection experiment

Abstract: Exposure to high levels of Zn generates variation in reproductive success among non-metallicolous individuals of Noccaea caerulescens. Descendant populations show slightly increased Zn tolerance and significantly decreased Zn hyperaccumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…(2016) showed earlier flowering in two invasive plant species in response to selection over few generations of water manipulations, and Nowak et al. (2018) demonstrated adaptive evolution of the Alpine Pennycress Noccaea caerulescens after one generation of exposure to various levels of zinc contamination in the soil. Due to multiple introductions and admixtures between differentiated populations, either prior or post‐introduction, invasive plants can exhibit large within‐population genetic diversity (Lavergne & Molofsky, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…(2016) showed earlier flowering in two invasive plant species in response to selection over few generations of water manipulations, and Nowak et al. (2018) demonstrated adaptive evolution of the Alpine Pennycress Noccaea caerulescens after one generation of exposure to various levels of zinc contamination in the soil. Due to multiple introductions and admixtures between differentiated populations, either prior or post‐introduction, invasive plants can exhibit large within‐population genetic diversity (Lavergne & Molofsky, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We need to consider that the studied moss plants here originated from a commercial source and were not optimized for phytoremediation. Plant clones could be further improved genetically through controlled growth under selective pressure to stimulate the up-regulation of resistance mechanisms [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Skroppa and Kohmann 48 demonstrated adaptation of Norway spruce ( Picea abies ) to local climatic conditions after only one generation, and Franks et al 49 found rapid evolution of flowering time in the annual Brassica rapa in response to climate change after just three generations. More recently, Nguyen et al 50 showed earlier flowering in two invasive plant species in response to selection over few generations of water manipulations, and Nowak et al 51 demonstrated adaptive evolution of the Alpine Pennycress Noccaea caerulescens after one generation of exposure to various levels of zinc contamination in the soil. Due to multiple introductions and admixtures between differentiated populations, either prior or post-introduction, invasive plants can exhibit large within-population genetic diversity 52 , This has also been found for ragweed in Europe 23,44,45 .…”
Section: Discussionmentioning
confidence: 99%